1995
DOI: 10.1159/000147688
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Merkel Cell Patterns in Developing Hair Follicles in the Dorsal Skin of Mice, Demonstrated by a Monoclonal Antibody to Mouse Keratin 8

Abstract: In order to explore the origin and significance of Merkel cells in the hairy skin of mammals, the development of Merkel cells and nerve endings in the dorsolateral skin of C57BL mouse embryos was studied in serial cryostat sections. At 13 and 14 days of gestation, application of a monoclonal antibody to mouse keratin 8 (mK8) resulted in specific immunofluorescence of all cells in the epidermis and periderm. The periderm retained specific staining until it was shed, around 18 days. At 15 days, mK8-specific stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 6 publications
(10 reference statements)
4
74
0
Order By: Relevance
“…These results might also explain why it has been previously reported that MCs originate from NCCs (Szeder et al, 2003). With the currently available tools and these mouse models, all evidence points to MCs being derived from epidermal cells, as has been previously suggested (Moll et al, 1986(Moll et al, , 1990Narisawa and Hashimoto, 1991;Moll and Moll, 1992;Cheng Chew and Leung, 1994;Vielkind et al, 1995), although a minor contribution of NCCs to MCs of the whisker region could not be entirely ruled out.…”
Section: Mcs Express Markers Of Embryonic Epidermal Progenitorsmentioning
confidence: 61%
See 3 more Smart Citations
“…These results might also explain why it has been previously reported that MCs originate from NCCs (Szeder et al, 2003). With the currently available tools and these mouse models, all evidence points to MCs being derived from epidermal cells, as has been previously suggested (Moll et al, 1986(Moll et al, , 1990Narisawa and Hashimoto, 1991;Moll and Moll, 1992;Cheng Chew and Leung, 1994;Vielkind et al, 1995), although a minor contribution of NCCs to MCs of the whisker region could not be entirely ruled out.…”
Section: Mcs Express Markers Of Embryonic Epidermal Progenitorsmentioning
confidence: 61%
“…Further evidence against the neural crest origin of MCs is their temporal appearance. MCs are present in the epidermis before the appearance of other neural crest derivatives such as nerve endings of the skin (Narisawa and Hashimoto, 1991;Cheng Chew and Leung, 1994;Vielkind et al, 1995). In humans, MCs are identifiable and transplantable several weeks before nerves reach the fetal epidermis (Moll et al, 1986(Moll et al, , 1990Moll and Moll, 1992), suggesting that MCs do not originate from NCCs.…”
Section: Mcs Originate From Embryonic Epidermal Progenitorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In mice, follicles and follicle-associated structures form on different schedules. Guard hair follicles and semicircular Merkel cell clusters are present by embryonic day (E) 16, and follicle-associated lanceolate nerve endings are present by postnatal day (P)0, but sebaceous glands and APMs develop postnatally (2,(10)(11)(12)(13).…”
mentioning
confidence: 99%